Impact of stator interturn short circuit fault on shaft voltage in a synchronous generator. Issue 3 (7th December 2022) - He, Yu‐Ling; Yang, Pei‐Jie; Sun, Kai; Xu, Zhen‐Li; Wang, Hai‐Peng; He, Xian‐Long; Gerada, David
Abstract: Shaft voltage often exists in synchronous generators due to the assembly error or various faults after the long‐term performance. The article investigates the shaft voltage characteristic under the stator interturn short circuit (SISC) condition. Different from other studies, this article mainly considers the mapping relationship between the amplitude–frequency characteristics of the shaft voltage and the SISC degrees. The detailed shaft voltage expressions are first derived based on the magnetic flux density under the normal condition and SISC condition. Then the finite element analysis and the experiment is studied on a CS‐5 prototype synchronous generator with two poles in order to validate the theoretical formula. The result shows that there is no shaft voltage in the normal condition, while the shaft voltage is generated obviously under the SISC condition. Meanwhile, the frequency component of the shaft voltage is mainly composed of odd harmonics including the first, third and fifth harmonics. Abstract : Shaft voltage often exists in synchronous generators due to the assembly error or various faults after the long‐term performance. This article investigates the shaft voltage properties due to the asymmetrical magnetic field under the stator interturn short circuit (SISC) condition. Different from other studies, this paper mainly considers the mapping relationship between the amplitude–frequency characteristics of the shaft voltage and the SISC degrees.